Institutional Pressures On Waqf Unit Trust Funds In Islamic Social Finance: The ASNB Wakalah Model For Social And Economic Impact - Syahnaz Sulaiman; Mushaddad Hasbullah; Nihat Gumus (Universiti Sains Islam Malaysia, 2026)
Waqf, as a perpetual charitable endowment, serves as a cornerstone for promoting social welfare and equitable wealth distribution within Islamic finance. Its integration into modern financial instruments, such as the Amanah Saham Nasional Berhad (ASNB) Wakalah Waqf Unit Trust, reflects a growing trend toward aligning Islamic capital market innovation with Islamic social finance objectives in Malaysia. This study examines the application of institutional theory in understanding the distribution of waqf benefits by ASNB Wakalah, focusing on how institutional pressures shape its governance, implementation, and social outcomes. Employing a qualitative document analysis approach, the research reviews policy documents, Islamic rulings (fatwas), prospectuses, annual reports, academic journals, books, and relevant online sources to evaluate ASNB’s waqf governance and distribution strategies. Despite ASNB’s pioneering role in developing a Wakalah-based waqf model, there remains limited scholarly attention to the institutional forces, such as regulatory frameworks, Shariah governance standards, and societal expectations that influence its operationalisation and impact. The findings reveal that ASNB’s waqf model is deeply embedded within Malaysia’s institutional environment, where compliance, legitimacy, and stakeholder expectations collectively shape its governance and distribution mechanisms. The study contributes to the growing body of knowledge on Islamic social finance and institutional theory. It also offers practical insights for policymakers and Islamic financial institutions to strengthen transparency, governance, and the social impact of waqf‑based investment schemes in line with institutional norms, ethical investment principles and Maqasid al-Shariah (Shariah objectives).